2006
DOI: 10.1111/j.1742-7843.2007.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of CYP1A2, CYP2D6 and CYP3A4 by Six Trade Herbal Products in Cultured Primary Human Hepatocytes

Abstract: The aim of this study was to evaluate the in vitro inductive potential of six commonly used trade herbal products on CYP1A2, CYP2D6 and CYP3A4 metabolic activities. Herbal components were extracted from the trade products in a way that ensured a composition equal to that present in the original product. Primary human hepatocytes and specific CYP substrates were used. Classic inducers were used as positive controls and herbal extracts were added in in vivo -relevant concentrations. Metabolites were determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 59 publications
5
81
0
1
Order By: Relevance
“…The authors conclude that both CYP 3A4 and P-gp interactions are unlikely to be clinically relevant, as the systemic concentrations are probably much lower; therefore, respective IC 50 values for P-gp cannot be reached in vivo. This conclusion is also applicable to their previous study [36] and to their study on CYP 2C19, which showed a weak induction by valerian root extracts [47].…”
Section: In Vitro Studiessupporting
confidence: 54%
See 3 more Smart Citations
“…The authors conclude that both CYP 3A4 and P-gp interactions are unlikely to be clinically relevant, as the systemic concentrations are probably much lower; therefore, respective IC 50 values for P-gp cannot be reached in vivo. This conclusion is also applicable to their previous study [36] and to their study on CYP 2C19, which showed a weak induction by valerian root extracts [47].…”
Section: In Vitro Studiessupporting
confidence: 54%
“…During the past decade, several potential mechanisms of interactions of valerian preparations, involving CYP enzymes, P-glycoprotein, and UGTs, have been studied in vitro [36,[38][39][40][41][42]46]. Some of these studies pointed to a possible drug interaction potential by valerian extracts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ginseng may increase cardiac repolarization and QTc interval 160 as well as proarrhythmic risk by additional increase in the bioavailability of antiarrhythmic agents due to reduced metabolism. 161 Siberian ginseng was reported to reproducibly elevate digoxin concentrations, which normalized after discontinuation and increased after resumption of ginseng. 162 Ginsenosides, which include more than 20 saponin glycosides with a nucleus similar in structure to steroid hormones, 163 can cause mastalgia, 164 functionally abnormal vaginal bleeding 165 and gynecomastia in males.…”
Section: Ginsengmentioning
confidence: 99%